Direct and Bystander Effect on Cervix Cancer Cells (SiHa) Exposed to High Dose-Rate Gamma Radiation Sourced from Ir 192 Used in Brachytherapy - Megha Anilkumar Kulkarni; Safa Abdul Syed Basheerudeen; Sidonia Vallas Xavier; Murugan Appaswamy; Thayalan Kuppusamy; Perumal Venkatachalam (International Journal of Radiology and Radiation Oncology - Peertechz Publications, 2015)
Introduction: Brachytherapy is a preferred choice of radiotherapy in the treatment of sensitive tissues  cancer  like  intestine  and  gonad.  The  treatment  is  expensive  because  of  the  frequent replacement of radionuclide sources. A better understanding of cell killing and the cellular responses at  different  dose  rates,  might  aid  in tumor  cell  killing  with  fewer  doses  thereby  enhancing  a  better prognosis. Methods: The cervix cancer cell line was irradiated with doses ranging from 2Gy-10 Gy at three different dose-rates as used in brachytherapy along with unexposed sample as control. The biological effects  of  different  doses  and  dose  rate  of  the  cells  was  assessed  by  measuring  its  cytotoxicity,genotoxicity  and  clonogenic  ability  of  exposed  cells.  The  bystander  effect  was  examined  by  co-culturing the exposed tumor cells with the unexposed normal blood lymphocyte and vice-versa.  Results: A significant and dose dependent changes in cell viability (trypan blue exclusion), genotoxicity (Micronucleus assay) and colony forming ability (Clonogenic assay) was observed in the cells exposed to different doses of radiation (p<0.0001); however, the changes were dose-rate independent.urthermore,  the  bystander  study  results  show  an  enhanced  cell  killing  in  the  tumor cells which suggest a beneficial bystander effects. Conclusion: The observed elevated bystander response in the tumour cells compared to that of normal blood lymphocytes suggest that if it happens under in-vivo situation, could results in has a therapeutic gain.